Unproclaimed Motivation: : A Sociological Analysis of Interventionalist Practices Against Censorship in Non-Professional Arabic Subtitling - Aljammaz, Abdulrahman Ibrahim (Journal of Audiovisual Translation, 2023)
With technological advances in AVT production, distribution, and consumption, translation activity has expanded to allow many opportunities for user participation such as non-professional subtitling. AVT scholars have thereby asserted that a new framework using a sociological lens is needed to study translators’ roles in non-professional settings. This paper focuses on the role of Arabic non-professional (ANP) subtitlers in their capacity as agents of normative change through activist practices. Namely, this paper tests the hypothesis that one of ANP subtitlers’ unproclaimed motivations behind subtitling is to challenge social and subtitling norms. Translating explicit language is presented as an example of this unproclaimed motivation to challenge censorship and ultimately social and subtitling norms. To this end, this paper relies on results obtained from a mixed-method survey that elicited sociodemographic data of 40 non-professional subtitlers of Arabic; as well as their motivations behind subtitling. This study has found that ANP subtitlers demonstrate activist practices by challenging censorship of explicit language. Activism is also identified as an unproclaimed motivation behind ANP subtitling. Survey responses and subtitling examples are analyzed and discussed followed by concluding remarks and recommendations for future research. Lay summary The development and spread of social media, the internet, and media production/distribution has bred new forms of translation that allow more participation from the viewers of films, YouTube videos, and any form of audiovisual content. This has blurred the line between so-called professional and amateur media production/distribution (Pérez-González, 2013a; Díaz-Cintas, 2018). Scholars who study the translation of audiovisual texts such as film using modes such as subtitling and dubbing have thereby stated that a new approach, using a sociological lens, is needed to study translators’ roles in non-professional settings. This paper focuses on Arabic non-professional (ANP) subtitlers in their capacity as agents of change through intervening in the translation. Intervention in the translation is manly revolved around controlling what is translated and how. Specifically, this paper tests the theory that one of ANP subtitlers’ unproclaimed motivations behind subtitling is to challenge societal and subtitling norms. Norms are a set of, mostly unwritten, rules that govern what is acceptable and what is not for a society or a subtitling community. Translating explicit language is presented as an example of this unproclaimed motivation to challenge norms as well as censorship that prevalent in many regulated media outlets such as Netflix, Amazon Prime, Disney+, etc. This paper presents results obtained from a survey of 40 non-professional subtitlers of Arabic; as well as their motivations behind subtitling. We found that 45% of the surveyed ANP subtitlers claim to adopt subtitling practices that may be called interventionist, and that this can also be seen in some of the examples of their texts. We also found that ANP subtitlers’ motivational factors have an impact on translational choices (for example, the choice of not translating certain words). These translational choices can be interpreted as forms of interventionism in some cases.